The Mycenaean Cemetery at Agios Vasileios, Chalandritsa, in Achaea - Aktypi, Konstantina, (Archaeopress Publishing Ltd, 2017)
The Mycenaean chamber-tomb cemetery at Agios Vasileios in Achaea, was first investigated in the late 1920s, followed by small-scale research in 1961. In the years 1989-2001 further rescue excavations revealed 30 chamber tombs, some looted. Based mostly on the latest research, this study is the first major presentation of the cemetery and its finds.